Brand personality : a research on Malaysian consumers' perception of Starbucks Coffee outlet / Bamini KPD Balakrishnan ... [et al.] - Balakrishnan, Bamini KPD; Lee, Samuel; Md.Shuaib, Azlinda Shazneem; Marmaya, Najihah Hanisah (Research Management Institute (RMI), 2011)
This study pertains to the use of the brand personality measurement framework as a means to investigate the pervasiveness of Starbucks, a foreign branded coffee outlet, in Malaysia. A survey was performed to obtain 261 consumer perceptions and opinions regarding the corporate branding of a foreign coffee outlet brand in Malaysia. Data was collected through the use of questionnaires from respondents in various cities throughout Malaysia using purposive and convenience sampling methods. Statistical analysis, including factor and reliability analysis, has been applied in order to statistically validate the findings ofthis research. The results of the analysis indicate that consumers identify Starbuck's to be distinctive and a confident brand.